AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. SINAR HARAPAN ANUGRAH SEJAHTERA MEDAN - Diana Diana; Sunarji Harahap; Elidawati Elidawati (STIE-PMCI, 2018)
This research conducted at PT. Sinar Harapan Anugrah Sejahtera Medan. As a company engaged in the field of snack food distributors, the company must have a good internal control of cash flow. Cash flow data can be said good if the entire accounting system of cash receipts dan disbursements meets the requirements of generally acceptes standards. The purpose if this study is to determine the accounting system of cash receipts and disbursements at PT. Sinar Harapan Anugrah Sejahtera Medan whether it is good or not. This type of research is descriptive research with case study at PT. Sinar harapan Anugrah Sejahtera Medan by analyzing the accounting of cash receipts and disbursements at PT. Sinar Harapan Anugrah Sejahtera Medan. Based on the results of the research, cash receipts system at PT. Sinar Harapan Anugrah Sejahtera Medan is still less good in terms of capture and segregation of duties and cases of cash larceny while for cash disbursement system at PT. Sinar Harapan Anugrah Sejahtera Medan has done well but still need a little change in the case of petty cash refill.Keywords: Cash Receipt, Cash Disbursement